How Does Nursing Staff Perceive the Use of Electronic Handover Reports? A Questionnaire-Based Study - Torbjørg Meum; Gro Wangensteen; Karen S. Soleng; Rolf Wynn (International Journal of Telemedicine and Applications)
Following the implementation of electronic nursing records in a psychogeriatric ward, we examined nursing staff's attitudes and perceptions to the implementation of an electronic handover routine. A web-based anonymous and secure questionnaire was distributed by e-mail to all nursing staff at a psychogeriatric ward at a university hospital. Most respondents were satisfied with the electronic handover, and they believed they managed to keep informed by the new routine. The simultaneous introduction of a morning meeting, to ensure a forum for oral professional discussion, was a success. A minority of staff did not fully trust the information conveyed in the electronic handover, and a significant proportion expressed a need for guidance in using the system. Staff that had a high level of trust in written reports believed these saved time, had little trouble finding time and a place to read the reports, and were more positive to the new handover routine.